Fluid replacement and heat stress (Committee on Military Nutrition Research; Food and Nutrition Board; Institute of Medicine; National Academy Press, 1994)
The content of the book: I Executive Summary (1-8) II Invited Papers (9-10) 2 Use of Electrolytes in Fluid Replacement Solutions: What Have We Learned from Intestinal Absorption Studies? (11-22) 3 Formulation of Carbohydrate-Electrolyte Beverages (23-36) 4 Considerations for Replacement Beverages: Fluid-Electrolyte Balance and Heat Illness (37-54) 5 Carbohydrate Supplements During and Immediately Post Exercise (55-68) 6 Gastric Emptying During Exercise: Influence of Carboyhydrate Source, and Exercise Intensity (69-84) 7 Interaction of Water Bioavailability Thermoregulation, and Exercise Performance (85-98) 8 Timing of Carbohydrate Supplementation During Prolonged Strenuous Exercise (99-110) 9 Acute Diarrheal Diseases (111-116) 10 Potassium Deficiency as the Result of Training in Hot Weather (117-126) 11 Shift in Body Fluid Compartments After Dehydration in Humans (127-142) 12 Role of Osmolality and Plasma Volume During Rehydration in Humans (143-160) 13 Palatability and Fluid Intake (161-168) 14 Solute Model or Cellular Energy Model? Practical and Theoretical Apects of Thirst During Exercise (169-194) 15 Environmental Issues That Influence Intake of Replacement Beverages (195-214) 16 Changes in Plasma Volume During Heat Exposure in Young and Older Men (215-228) Index (229-242)